Classroom Management in Schools - Rijal, Chanakya P (Journal of NELTA Surkhet, 2015)
Among the various concepts emerged more recently in the field of formal education, especially in school education, classroom management has been considered as one of the integrated functions of institutional and functional intervention areas in teaching-learning. In this discourse, different professionals and institutions happen to proclaim different strategies and functional inputs so as to transform classroom as one of the most essential areas of school transformation. The scope of functional coverage of classroom management has expanded significantly these days from the concept of traditional physical structural shape to induction of newer approaches of student participation, learner focused teaching learning, collaborative and cooperative approaches to teaching-learning materials development and implementation, making classroom discourses more socio-ethically sound, and creating appealing classroom infrastructure and rules for teachers, students and also for the parents. In fact, there is no readymade capsule to swallow as the final solution for this issue and there is also no final destiny as the overall concept of classroom and its arrangement has been consistently overhauled globally. Journal of NELTA Surkhet Vol.4 2014: 48-56